2020
DOI: 10.1038/s41598-020-73415-3
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cortical thickness reduction and disconnection in high myopia

Abstract: High myopia (HM) is associated with impaired long-distance vision. accumulating evidences reported that abnormal visual experience leads to dysfunction in brain activity in HM even corrected. However, whether the long-term of abnormal visual experience lead to neuroanatomical changes remain unknown, the aim at this study is to investigate the alternation of cortical surface thickness in HM patients. 82 patients with HM (HM groups), 57 healthy controls (HC groups) were recruited. All participants underwent high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
(54 reference statements)
1
14
0
Order By: Relevance
“…Recently, Wai, et al [33] reported a relationship between visual function and deep retinal perfusion density as measured by microperimetry and OCTA respectively, suggesting that these parameters may serve as early indicators of structural and functional abnormalities in highly myopic eyes with myopic macular degeneration (MMD). Published neurological and functional magnetic resonance imaging studies have previously identified functional alterations across multiple cortical layers in brains of patients with highly myopic eyes [34]. In the future, we plan to investigate the structural and functional postoperative findings in surgically resolved myopic FRD to test whether this macular pathology further leads to the aggravation of cortical surface thickness and related functional connectivity in MMD patients.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Wai, et al [33] reported a relationship between visual function and deep retinal perfusion density as measured by microperimetry and OCTA respectively, suggesting that these parameters may serve as early indicators of structural and functional abnormalities in highly myopic eyes with myopic macular degeneration (MMD). Published neurological and functional magnetic resonance imaging studies have previously identified functional alterations across multiple cortical layers in brains of patients with highly myopic eyes [34]. In the future, we plan to investigate the structural and functional postoperative findings in surgically resolved myopic FRD to test whether this macular pathology further leads to the aggravation of cortical surface thickness and related functional connectivity in MMD patients.…”
Section: Discussionmentioning
confidence: 97%
“…2 b & c) fell within the range for resolution acuity at or close to 15° eccentricity of peripheral visual field ranges from 2.5 to 12 arcmin reported by previous studies. 20 , 36 , 37 The wide variations in measured peripheral resolution acuity obtained by previous studies could be attributable to the differences in psychophysical methods (method of adjustment, 20 2-up 1-down staircase, 33 and 1-up 1-down staircase 34 ), tested visual field locations, and participants’ refractive errors. Third, this study measured resolution acuity rather than detection acuity (i.e., identifying the presence or absence of gratings), even though the latter is also a common spatial acuity parameter.…”
Section: Discussionmentioning
confidence: 98%
“…31 Furthermore, recent studies have also revealed functional connectivity and morphological changes in the brains of high myopes, even though their best-corrected distance visual acuity was normal. [32][33][34] To remove the potential contribution of myopia to meridional anisotropy at peripheral visual fields, participants with emmetropia were recruited as a control group. However, no significant difference in the meridional anisotropy between the SM and EM groups was observed across all tested retinal locations.…”
Section: Discussionmentioning
confidence: 99%
“…The occipital lobe not only plays an important role in integrating information of visual sense, auditory sense, and other information gathered by sensory systems but also connects visual information with brain processing systems of speech and other executive functions (Wu et al, 2020 ). The parietal lobe is essential to process sensory information, including integration, perception, digital cognition, speech understanding, decision-making, and spatial consciousness (Critchleey, 1953 ; Bisley and Goldberg, 2010 ).…”
Section: Discussionmentioning
confidence: 99%